BENEFITS OF INSTAGRAM USAGE AND ITS EFFECTIVENESS IN TEACHING ENGLISH: A SYSTEMATIC REVIEW - Siti Nurhakiki; Yati Nurhayati; Pita Septi Tri Amalia; Naf’an Tarihoran (Adisam Publisher, 2025)
Recently, social media platform usage in the context of educational settings has changed the way students learn and teachers teach. And one such platform is Instagram. This article aims to explore the benefits of using Instagram in the classroom to teach English and examine its effectiveness in teaching English and improving language proficiency based on previous research. Therefore, this article utilizes the systematic review method. A total of 106 articles were collected through several databases namely Eric, Google Scholar, and DOAJ, and selected until 25 articles were selected to be analyzed. The results of the analysis show that the utilization of Instagram is very effective in increasing all language skills such as writing, speaking, reading as well as listening. Instagram is also effective in increasing students' vocabulary and increasing students' interest and motivation to learn English. Instagram as a learning media is also beneficial to create a learning process that tends to be more interesting and flexible. The content on Instagram is very useful for increasing students' creativity because students can find more ideas on Instagram. In terms of providing feedback to students, Instagram is a very effective application through its features.